Utilization of VN Application as a Learning Media for Social Education at Elementary School Level - Rohmawaty, Evy Nur; Wahyuni, Sri; Ginarti, Ginarti (International Journal of Language and Ubiquitous Learning, 2023)
Background. The downside of distance learning activities is that students lack enthusiasm, which results in disappointment in learning outcomes. The problem is due to the lack of tools and opportunities that are not maximized by educators during learning activities. Purpose: The purpose of this study is to optimize the performance of VN applications to motivate and improve student comprehension skills in learning natural science at the elementary school level. Method. The method used in this research includes direct field research which is a research method with a qualitative descriptive approach. Descriptive which describes the condition of students in classroom learning activities and makes the VN application and students as the object of research. This approach provides a real explanation of how much influence the utilization of the VN application to describe the learning material obtained in accordance with the learning design of the teacher. Results: Based on the results of my research, the utilization of video-based learning media using the VN editor application has a positive impact on the learning process at the elementary school level. Conclusion. based on the discussion in this study, it can be concluded that the use of the VN application is very useful in the learning process of students at the elementary school level. Especially in this study on social science subjects.